Context-aware scheduling in Fog computing: A survey, taxonomy, challenges and future directions - Islam, Mir Salim Ul; Kumar, Ashok; Hu, Yu-Chen (Journal of network and computer applications, 2021)
Fog computing extends Cloud-based facilities and stays in the vicinity of the end-users to provide an attractive solution to a diverse range of latency-sensitive applications. The applications are becoming more sophisticated, context-aware, and computation-intensive due to varying situational and environmental conditions in order to meet the ever-increasing users’ demands. Further, resource heterogeneity, dynamic nature, resource limitations, and unpredictability of the Fog environment make scheduling of application tasks while satisfying Quality of Service (QoS) requirements a challenging job. To overcome these issues various scheduling strategies have been proposed considering contextual information of different entities involved in Fog computing. This survey represents a comprehensive literature analysis pertaining to context-aware scheduling in Fog computing. It provides detailed comparison of existing scheduling approaches based on important factors such as context-aware parameters, case studies, performance metrics, and evaluation tools along with advantages and limitations. It also presents detailed taxonomy, performance metrics, and context-aware parameter analysis. Further, it list several issues and challenges. This study will aid the research community in exploring future research directions and essential aspects of scheduling approaches using different types of contextual information.